2017
DOI: 10.3389/fpsyg.2017.00119
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Personality Traits in Young Adult Fruit and Vegetable Consumption

Abstract: This project investigated how individual differences in the big-five personality traits (neuroticism, extraversion, openness to experience, conscientiousness, and agreeableness) predicted plant-food consumption in young adults. A total of 1073 participants from two samples of young adults aged 17–25 reported their daily servings of fruits, vegetables, and two unhealthy foods for comparison purposes using an Internet daily diary for 21 or 13 days (micro-longitudinal, correlational design). Participants also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 50 publications
(98 reference statements)
6
62
0
Order By: Relevance
“…The finding that conscientiousness is the most important personality trait for fruit and vegetable consumption is consistent with findings observed in adult samples (Allen et al, ; Conner et al, ; Keller & Siegrist, ). However, the current study does not support previous work that also found a small positive association between extraversion and fruit and vegetable intake (Conner et al, ; Keller & Siegrist, ). An important new finding was that personality trait change over 2 years related to healthy eating.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that conscientiousness is the most important personality trait for fruit and vegetable consumption is consistent with findings observed in adult samples (Allen et al, ; Conner et al, ; Keller & Siegrist, ). However, the current study does not support previous work that also found a small positive association between extraversion and fruit and vegetable intake (Conner et al, ; Keller & Siegrist, ). An important new finding was that personality trait change over 2 years related to healthy eating.…”
Section: Discussionsupporting
confidence: 89%
“…Conscientiousness has been negatively associated with unhealthy eating (Bogg & Roberts, 2004), while extraversion and openness have been shown to have positive relationships with healthy eating (Brummet et al, 2008;Keller & Siegrist, 2015). Steptoe et al (1995) also reported that willingness to try new foods is related to openness, and Conner et al (2017) found that openness and extraversion were related to greater fruit and vegetable consumption in young adults.…”
Section: Individual Differences Between Vegetarians and Meat Eatersmentioning
confidence: 99%
“…In this study, the conscientiousness subtraits of order, concentration, and perseverance underline the importance of executive functioning, behavioral adaptation, and low impulsiveness for regularity in eating. Imagination explained correlated with lower fussiness and enjoyment of food, findings paralleling the healthier food choices in adults with high Openness to experience fish and more fruit and vegetables [ 19 ].…”
Section: Main Textmentioning
confidence: 99%